Статистичні дослідження несправностей автомобілів-тягачів MERCEDES-BENZ у гарантійний і післягарантійний періоди експлуатації - Кравченко, Олександр; Верітельник, Євген (КІНПАТРІ ЛТД, 2013)
The ground-states of semi-trucks are educed in the process of warranty and post-warranty periods of exploitation and reasons of their outages are set; reliable aggregates, knots and details of semi-trucks, in operating terms are certain. Laws of distributions allowing to forecast the origin of refuses are got.
Statistical researches of failures of cars-tractors MERCEDES-BENZ during warranty and post-warranty exploitation periods